B-SPLINE COLLOCATION METHOD FOR NUMERICAL SOLUTION OF NONLINEAR KAWAHARA AND MODIFIED KAWAHARA EQUATIONS - Bagherzadeh, Amir Saboor (TWMS journal of applied and engineering mathematics, 2017)
In this paper, a collocation method is applied for solving the Kawahara and modified Kawahara equations. For the spatial discretization, we use the sextic B-spline collocation (SBSC) method on uniform meshes, finite difference scheme is employed for the time discretization. The stability analysis of the collocation methods are examined by the Von Neumann approach. Numerical results demonstrate the efficiency and accuracy of the proposed methods.Keywords: Kawahara and modified Kawahara equation, sixth degree B-splines, collocation method, recurrence system of equations, stability analysis, numerical experience.AMS Subject Classification: 83-02, 99A00